2017
DOI: 10.5897/ajps2017.1528
|View full text |Cite
|
Sign up to set email alerts
|

Growth, symbiotic and yield response of N-fertilized and Rhizobium inoculated common bean (Phaseolus vulgaris L.)

Abstract: Common bean (Phaseolus vulgaris L.) is one of the most important and widely cultivated pulse crops in most developing countries. However, its cultivation is globally constrained mainly by low soil fertility and lack of improved agronomic practices. A field experiment was conducted at Hawassa University College of Agriculture, Hawassa Southern Ethiopia to determine the effect of N fertilization and Rhizobium phaseoli strain HB-429 inoculation on growth, nodulation, yield and yield components of common bean vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Similar to this result Haruna and Usman [ 44 ] observed a significant variation in grain yield of some improved varieties of cowpea and attributed it to the genetic makeup of the varieties examined. The results coincide with the findings of Tarekegn and Serawit [ 45 ], who concluded improved seed yield due to Rhizobium inoculation in haricot bean varieties. Lower grain yield from M1 : 1CB arrangement might be associated with the microclimate effects of maize canopy and higher competition due to the extensive root system of maize.…”
Section: Resultssupporting
confidence: 91%
“…Similar to this result Haruna and Usman [ 44 ] observed a significant variation in grain yield of some improved varieties of cowpea and attributed it to the genetic makeup of the varieties examined. The results coincide with the findings of Tarekegn and Serawit [ 45 ], who concluded improved seed yield due to Rhizobium inoculation in haricot bean varieties. Lower grain yield from M1 : 1CB arrangement might be associated with the microclimate effects of maize canopy and higher competition due to the extensive root system of maize.…”
Section: Resultssupporting
confidence: 91%
“…It comprises an irregular polygon and a set of lines drawn from the biplot origin which intersect each of the sides at right angles (Yan et al, 2007). The vertices of the polygon are the genotype markers located farthest away from the biplot origin in various directions, in a way from the biplot origin in various directions, in a way that all genotype markers are contained within the resulting polygon (Tarekegn and Serawit, 2017). A line that starts from the biplot origin and perpendicularly intersects the polygon side represents the set of supposed environments in which the two genotypes defining that side perform equally.…”
Section: Gge Biplot Analysis For Grain Yields In Multienvironmentmentioning
confidence: 99%
“…Various studies have assessed the strategies that improve bean growth and yields, among them are use of appropriate organic and inorganic fertilizers, nitrogen fixing rhizobia, irrigation, spacing and crop configuration, pest and disease management (Naser et al, 2013;Ibrahim, 2012;Vanlauwe et al, 2019;Campos et al, 2021). Several studies have reported on growth and yield responses of different common bean varieties to various fertilizers or inoculation (Ndakidemi and Dakora, 2007;Shumi, 2018), water stress/drought tolerant (Asemanrafat and Honar, 2017;Karantin et al, 2019;Mbiu et al, 2020a), irrigation methods (Ibrahim et al, 2017;Campos et al, 2021), maize-legumes intercropping (Yoseph and Shanko, 2017) or combination of plant density/spacing with fertilizers (Kiriba et al, 2020). However, few studies have assessed the yield responses of various common bean varieties to a range of high planting densities.…”
Section: Introductionmentioning
confidence: 99%
“…Common bean cultivation is rapidly expanding in Ethiopia, primarily due to its fast maturation, which enables early income generation from both domestic and export markets [11][12][13]. Despite its versatility, production faces challenges, such as low soil fertility, nutrient imbalances, land degradation, soil acidity, drought, and heat [14,15]. Many of these challenges can be addressed through breeding and agronomic interventions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these challenges can be addressed through breeding and agronomic interventions [15]. Declining soil fertility poses a signifcant obstacle to common bean production, necessitating an adequate and balanced nutrient supply for optimal yield [14].…”
Section: Introductionmentioning
confidence: 99%